2011
DOI: 10.1179/1743285510y.0000000009
|View full text |Cite
|
Sign up to set email alerts
|

Surface and chemical properties of chlorite in relation to its flotation and depression

Abstract: The chlorite group of minerals exhibit a wide range of surface charging properties in aqueous suspensions. A systematic review of the literature as it relates to the flotation, depression and surface properties of chlorite and related minerals was undertaken, with a view to using this information to help develop suitable reagent schemes which might allow the selective removal of chlorite from sulphide and oxide flotation systems. The surface charge on chlorite mineral particles originates from permanent charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…However, these two phyllosilicates have different crystal structures and surface properties and further affect flotation in different ways. Chlorite is a 2:1 phyllosilicate with an interlayer brucite-like sheet containing Mg, Al, and Fe octahedrally coordinated [13]. After the liberation, there are broken bonds of the brucite-like sheet, which cause staggered charged surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these two phyllosilicates have different crystal structures and surface properties and further affect flotation in different ways. Chlorite is a 2:1 phyllosilicate with an interlayer brucite-like sheet containing Mg, Al, and Fe octahedrally coordinated [13]. After the liberation, there are broken bonds of the brucite-like sheet, which cause staggered charged surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The depression of chlorite is achieved by increasing its surface hydrophilic ability, thus reducing its floatability. The depressants primarily include sodium silicate, hydrogen fluoride, tripolyphosphate, and a variety of other polysaccharides [13]. For serpentine, however, the depression is principally achieved by creating electrical repulsion or steric hindrance to disperse serpentine from valuable particles' surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that starch was not a selective depressant for magnetite in the process of the reverse cationic flotation of iron ores when iron-containing silicates as amphiboles are present in the flotation system [8]. Carboxymethyl cellulose, an effective depressant for iron oxide, was also found to be a depressant for chlorite [14].The novel high-efficiency depressants or collectors are considered to be an effective method to solve the unsatisfactory separation problems [15,16]. These depressants and collectors are targeted for making a sufficient hydrophilic and hydrophobic state of the mineral and gangue surface, respectively.…”
mentioning
confidence: 99%
“…They also found that starch was not a selective depressant for magnetite in the process of the reverse cationic flotation of iron ores when iron-containing silicates as amphiboles are present in the flotation system [8]. Carboxymethyl cellulose, an effective depressant for iron oxide, was also found to be a depressant for chlorite [14].…”
mentioning
confidence: 99%
“…Chlorite distributes in nature widely and is one of the most common minerals in sedimentary, low-grade metamorphic, and hydrothermal metamorphic rocks [1][2][3]. Reports of the separation of chlorite and other minerals are often seen [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%